Zoonoses The ties that bind humans to animals - Vourc'h, Gwenaël (éditions Quae, 2022)
Animals are all around us. We overlap with them in environments across the globe, which leads to myriad interactions, including shared infectious and parasitic diseases. Such diseases, known as zoonoses, are the focus of this book. Within its pages, the authors describe the nature and transmission of zoonoses, discuss the diseases of greatest concern, detail different protective measures, and examine the factors responsible for zoonosis emergence and evolution. This work encourages readers to delve deeper into the world of animals and microbes that surrounds us. It presents knowledge we must possess to better protect ourselves and, more importantly, to adopt a more holistic approach to our relationships with animals and the living world.